Penggunaan Testlet dalam Pengembangan Tes Psikologi - Wahyu Widhiarso (Airlangga University Press, Universitas Airlangga, 2018)
Abstract. The unit of analysis or measurement is not always item level, but also group of items (testlet). This paper demonstrates the development of measurement using testlet that are rarely applied in Indonesia. The example used in this paper is the development of the measurement of visual ability, one of several test included in AJT COGTEST. In this test, the basis of grouping items into testlet is their similarity of figure being referenced. This test consists of fifteen figure and each figure consists of seven items. The data analysis technique used is the Rasch Model. The result of comparison shows the advantages testlet psychometric properties as compared to item as unit of analysis. The data generated from testlet tends to be unidimensional, not infected local dependencies, high discrimination and high model fit than the unit of analysis in the form of grains. The comparison function test information indicates that the use testlet enhance test information function. In general, the concept of testlet and applications through Winsteps program in the development of measurement tools in presented in this paper.Keywords: Measurement Unit; Rasch Model; Testlet Abstrak. Unit pengukuran tidak selalu berbentuk butir, akan tetapi juga dapat berbentuk kelompok butir (testlet). Tulisan ini mendemonstrasikan pengembangan alat ukur dengan menggunakan testlet yang jarang diterapkan di Indonesia. Contoh yang dipakai dalam tulisan ini adalah pengembangan pengukuran abilitas visual bagian dari AJT COGTEST. Dasar pengelompokan butir menjadi satu testlet adalah kesamaan gambar yang diacu karena beberapa butir mengacu pada gambar yang berbeda. Teknik analisis data yang dipakai adalah Model Rasch. Hasil perbandingan properti psikometris menunjukkan kelebihan testlet dibanding dengan butir. Data yang dihasilkan dari testlet cenderung bersifat unidimensi, tidak terjangkit dependensi lokal, memiliki ketepatan model dan daya diskriminasi butir yang lebih baik dibanding dengan unit analisis berupa butir. Hasil perbandingan fungsi informasi tes menunjukkan bahwa penggunaan testlet meningkatkan fungsi informasi tes. Secara umum konsep mengenai testlet dan aplikasinya melalui program Winsteps dalam pengembangan alat ukur dalam dipaparkan dalam tulisan ini.Kata Kunci : Testlet; Unit Pengukuran; Model Rasch